METHODS OF USING SPENT BLEACHING CLAYS (Web of Technology: Multidimensional Research Journal, 2025)
Vegetable oils undergo multi-stage purification processes. In the process of oil bleaching, special clays containing all the macro- and microelements necessary for a living organism are used as adsorbents: The article describes the methods for processing used adsorbents. In particular, a method is proposed for using waste generated in the process of adsorption refining of vegetable oils as additives for enriching feed meal.